THEORETICAL STUDY OF THE PLASMON IN GOLD NANOSPHERES - Osorio Anaya, Ana María (2019)
In the present work the simulation of the plasmonic behavior of gold nanospheres with diameters of 10, 20, 30, 40, 50 y 60 nm in aqueous medium against light with wavelenghts ranging from 400 to 650 nm was done. A greater contribution of the scattering to the extinction spectrum was observed as a function of the size of the nanosphere, which exhibited an exponential behavior.